Serum Adiponectin Levels in Advanced-Stage Parkinson's Disease Patients - Erica Cassani; Raffaella Cancello; Ferruccio Cavanna; Sabrina Maestrini; Anna Maria Di Blasio; Antonio Liuzzi; Gianni Pezzoli; Michela Barichella (Parkinson's Disease)
Patients with advanced Parkinson's disease (PD) experience body weight loss and reductions in the most common cardiovascular risk factors. At present, the pathogenetic mechanisms involved have not been elucidated. Increased serum concentrations of adiponectin, which possesses antiatherogenic and anti-inflammatory properties, are associated with a reduction in cardiovascular risk. The objective of this study was to determine adiponectin serum concentrations in PD patients. Thirty PD patients underwent a full nutritional status assessment, including the determination of adiponectin serum concentrations. Mean ± SD adiponectin concentrations were 9.59 ± 5.9 μg/mL (interquartile range: 5.92–12.9 μg/mL). In PD patients, adiponectin serum levels were similar to those in normal-weight, healthy, young subjects and significantly higher than that in an aged-matched group of morbidly obese subjects. Further studies are warranted to establish the role of adiponectin in the management of PD patients.